The influence of perceptual factors on visual word recognition: a review of the literature in expert and dyslexic readers - Civera, Teresa; Perea, Manuel; Vergara-Martínez, Marta (Revista de Investigación en Logopedia, 2025)
For expert readers, reading is a straightforward and automated process that facilitates access to meaning. However, all readers initially go through a stage where this process is effortful and demanding. This transition occurs due to the use of different reading strategies. While learning to read, we rely on an alphabetic/serial strategy, but as we gain automaticity, we shift to parallel reading. Expert readers flexibly alternate between these strategies depending on the orthographic demands of each stimulus to facilitate lexical access. Multiple perceptual factors vary across the words we read. For instance, we may encounter the same word presented like this, like this, LIKE THIS or like this. Although we are initially more sensitive to such perceptual variations, reading development leads to increased tolerance. However, does the same occur in individuals with dyslexia? In this paper, we present a theoretical review of perceptual factors in reading and their impact on dyslexia.